More similar firms - More similar regions? On the role of firm heterogeneity for agglomeration - Maximilian von Ehrlich; Tobias Seidel (Center for Economic Studies and ifo Institute (CESifo), 2012)
In contrast to what several papers have argued recently, we show that firm heterogeneity fosters agglomeration of economic activity. If firms are more similar with respect to their total factor productivity, each company faces a lower propensity to export. This renders the home market more important speaking against agglomeration. We also relate changes in firm heterogeneity to technological progress which allows us to derive novel insights on the role of technology for the location of economic activity.
Keywords: F12; F22; R12; 330; firm heterogeneity; agglomeration; technological change; trade; labor mobility; Unternehmen; Produktivität; Ballungsraum; Regionales Cluster; Technischer Fortschritt; Standortwahl; Theorie